Sustainability of GUINÉ-BISSAU-Application of the action of Standards ISO 9001, 14001, 26000 and 45001 - Baía, Amândio Pereira; Silva, Carla Correia (Archives of Business Research, 2023)
Sustainability represents one of the greatest challenges of the millennium. Many countries have already implemented ISO standards on Management, Quality, Environment and Occupational Safety and Health systems. In Guinea-Bissau, the poor quality of management, forest deforestation, the extinction of several species of fauna and flora, the difficulties of collecting and treating waste, the non-compliance by companies with occupational safety and health standards, and the lack of business ethics in the process of operationalizing the activities of companies, aroused the interest in showing the relevance of the implementation of ISO standards - Quality Management (9001), Environment (14001), Safety and Health at Work (45001) and Social Responsibility (26000) in this country. The implementation of ISO standards in Guinea-Bissau will oblige organizations to comply with quality standards that will contribute to the improvement of the quality of life of Guineans and the sustainability of the planet.